The Challenges HRM Must Face under Flexible Work Arrangements (Case of the Slovak Republic) - Bajzikova, Lubica; Sajgalikova, Helena (Ekonomika, 2004)
The research seeks to examine the background to the growing importance of this theme in Europe, the views and strategies of the parties involved (employers, employees, and governments), the impact of the new legislation and the application of labour flexibility in new market economies. The research finds that it is unfortunate that only incomplete and disparate statistics and analyses are currently available. An international comparison in this area can thus be only of a quality nature. The regulation of working time in Western Europe followed a number of rules which steadily became general throughout the continent, The application of the new forms (functional flexibility, financial/wage flexibility, labour mobility flexible patterns and organisation of work) is gradually introduced, mapping the employment developments of the EU Member States. However, the application of the policies in practice is mostly more difficult than expected and the implementation problems differ from one form to another. The problems identified in the Slovak Republic can be summarized as follows: gaps in legislation, insufficient managerial competencies to master new flexible forms, rigidness of working habits of both managers and employees, cultural barriers.